1996
DOI: 10.1111/j.0953-0673.1996.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate for the treatment of refractory Crohn's disease.

Abstract: Methotrexate appears effective in most patients with refractory Crohn's disease and its short-term toxicity is acceptable, but the long-term benefit seems more limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 0 publications
1
23
0
1
Order By: Relevance
“…14 Two larger studies, conducted in France and Scotland, 16,17 both reported response rates to therapy in the order of 70%, but approximately 40% were in remission at 12 months in the French cohort, 16 compared with only 20% in the Scottish study. 17 The higher remission rates in the French study may relate to the fact that the patients selected for inclusion were only those who exhibited a good initial response to methotrexate, with those with early relapse or intolerance to therapy excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Two larger studies, conducted in France and Scotland, 16,17 both reported response rates to therapy in the order of 70%, but approximately 40% were in remission at 12 months in the French cohort, 16 compared with only 20% in the Scottish study. 17 The higher remission rates in the French study may relate to the fact that the patients selected for inclusion were only those who exhibited a good initial response to methotrexate, with those with early relapse or intolerance to therapy excluded.…”
Section: Discussionmentioning
confidence: 99%
“…17 The higher remission rates in the French study may relate to the fact that the patients selected for inclusion were only those who exhibited a good initial response to methotrexate, with those with early relapse or intolerance to therapy excluded. 16 In another study, which administered 25 mg of intramuscular methotrexate to 14 patients with refractory CD for 12 weeks, 13 36% and 29% of patients achieved endoscopic and histological remission, respectively. Although these response rates are substantially lower, it should be noted that these outcome measures were appreciably more stringent than the clinical assessments conducted in most of the other studies, and in fact clinical response was achieved in approximately 80% of these patients at 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional reports on the utility of methotrexate in steroid-refractory patients are available, but these reports are mostly case series [81,82,83]. The remission rate in these three series which mostly included patients intolerant of or refractory to purine analogues was about 70%.…”
Section: Steroid-refractory and Steroid-dependent Diseasementioning
confidence: 99%
“…Additional reports on the utility of methotrexate in steroid-refractory patients are available, but these reports are mostly case series [59,60,61]. The remission rate in these three series which included mostly patients intolerant of or refractory to purine analogues was about 70%.…”
Section: Steroid-refractory and Steroid-dependent Diseasementioning
confidence: 99%